Does life satisfaction vary with income inequality and social mobility?. Issue 1 (2022) - Suriyanrattakorn, Savinee; Chang, Chia-Lin
Abstract: This article provides a novel analysis using the Global Social Mobility Index (GSMI) in order to explore whether the relationship between income inequality and life satisfaction differs depending on the level of social mobility. Unlike typical social mobility proxies, such as intergenerational persistence in education, the GSMI (by the World Economic Forum) views mobility as a broad concept which captures both quantity and quality which results in a more precise measure. Using a cross-country panel dataset (143 countries, 2005–2020), the main results indicate that, overall, a higher level of income inequality is related with a lower national average life satisfaction. Furthermore, the findings support the tunnel effect hypothesis showing that the negative relationship between income inequality and life satisfaction is more prevalent in groups with lower social mobility. The contributions of this study are devoted to the area of wellbeing policy development. Policies aimed at promoting income equality are recommended to improve the overall life satisfaction of citizens, especially for countries with low social mobility.